Reconfiguring TDMA Communications for Dynamic Formation of Vehicle Platoons - Aslam, Aqsa (2020)
Platooning is a promising concept used within the Intelligent Transportation System to increase efficiency and safety of road transportation. It is based on periodically sharing the kinematic status of the platoon members to allow reducing inter-vehicle distances in a safe way. This coordination is automatic and depends heavily on the wireless channel. A common technique to improve the channel properties is to use Time-Division Multiple Access (TDMA) that organizes the access to the wireless medium in slots assigned exclusively to each vehicle. However, while platoons are physical and dynamic, the corresponding dynamic reconfiguration of a logical TDMA frame is non-trivial. In this paper we address this Cyber-Physical problem resorting to the RA-TDMAp protocol to track the dynamics of a platoon, specifically joining, merging and leaving. In our solution, we include an adequate admission control block, to verify whether joining or merging can be accepted, and we present the state-machine that handles the reconfiguration process. We validate our TDMA reconfiguration mechanism with simulations using the Plexe/Vein/OMNeT++ framework. We show the effectiveness of the proposed mechanisms which ensures a synchronized start of the platoon control with the TDMA frame reconfiguration.